Oceans [videorecording (DVD)] - Brosnan, Pierce (Walt Disney Studios Home Entertainment, 2010)
Features an exhilarating look under the sea through the eyes of those that live there. Incredible state-of-the-art-underwater filmmaking will take viewers breath away as they migrate with whales, swim alongside a great white shark, and race with dolphins at play. Includes first-ever images of elusive deepwater creatures, featurettes, music video, filmmaker annotations, and more.